Globalization - the challenge of new times - Gordana Bujas (European Regional Science Association (ERSA), 2001)
The world economy undergoes through big changes and enters into the restructuring and reorganization process, which bring some countries into the new situations and faces them and their enterprises with new tasks. Knowledge has primary role, both for the individual and overall economy in this changing world, while the land, work and capital become of secondary importance. Creation and innovation enter into the way of production as its most important parts. Globalization brought by the scientific-technological revolution radically change the picture of the world, being result of increase of inter-relations in technololgical progress, which is especially important for the countries that are developing on information technologies. Globalization process is usually linked to the market, financial system, competition and corporate strategy. The globalization process enables and stimulates the removal of custom and non-custom barriers and deregulation of market expansion, what results with accelerated increase of supply, stabilization and often with decrease of prices. Such effect is determined as "supply shock", what means that the demand is in upturn by increase of supply and pressure on prices, opening the room to the enterprises for increase of production and turnover and simultaneously stimulates the adjustment to the changed market terms and qualification for European and world competition. Meanwhile, in order to realize such globalization process, it would be necessary to coordinate the macroeconomic context and economic policies of individual countries, which have been reducing macroeconomic limitatiosn and open room for global movements. As a result of coordination of macroeconomic contexts, the global economic regions on regional basis are being formed, while the customs, monetary and fiscal systems have the central place as result of coordination of macroeconomic policies and macroeconimic coordination, out of them the monetary, customs and foreign exchange rate policies being in the function of the economy stabilization and achievemnt of the high economic growth rates. Since globalization has the large impact on the economy as a whole as well as for their companies, in this paper we will try to analyze its advantages and usefulness, fears and uncertainties brought along with it , as well as the place of Croatia in such a process.
Keywords: 330